Can criminal law protect the environment? - Rées, Helena du (Journal of Scandinavian studies in criminology and crime prevention, 2002)
This article examines the question of whether criminal law can protect the environment by functioning as a means of controlling environmentally hazardous activities. The concept of general prevention today dominates in the context of criminalization, and has been particularly emphasized in relation to criminalizations whose objective is environmental protection. The article discusses the conditions for general prevention in the context of environmental criminal law. These conditions include the regulatory acumen of those applying the law, the likelihood of being sanctioned for offences and the severity of sanctions imposed. Further, the article identifies problems faced by the agencies whose task it is to apply environmental criminal law. The most conspicuous of these problems is the dual role of the supervisory which function both as advisers and enforcers in relation to the operations that they monitor. Police and prosecutors are primarily faced with problems of a legal-technical nature, such as difficulties proving offences have been committed and investigating the question of responsibility, and problems of competency. These competency issues include difficulties applying the regulatory framework of the criminal law and a lack of expertise in the area of natural science. Finally, explanations are sought for the problems experienced in applying environmental criminal law. The agencies, article concludes that the fundamental causes of these problems lie in the way the environmental crime legislation is based on the weighing of competing interests against one another, and the unclear role of the supervisory authorities that constitute the first link in the judicial chain. This lack of clarity gives rise to an uneven application of the legislation and causes problems for those applying the law at higher levels within the justice system